2020
DOI: 10.3174/ajnr.a6937
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Hyperpolarized 13C Metabolic Imaging in Pediatric Patients with Diffuse Intrinsic Pontine Glioma and Other CNS Cancers

Abstract: BACKGROUND AND PURPOSE: Pediatric CNS tumors commonly present challenges for radiographic interpretation on conventional MR imaging. This study sought to investigate the safety and tolerability of hyperpolarized carbon-13 (HP-13 C) metabolic imaging in pediatric patients with brain tumors. MATERIALS AND METHODS: Pediatric patients 3 to 18 years of age who were previously diagnosed with a brain tumor and could undergo MR imaging without sedation were eligible to enroll in this safety study of HP [1-13 C]pyruvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Hyperpolarized carbon-13 (HP-13C) MR imaging presents a promising relatively new technique that allows noninvasive investigation of in vivo tumor metabolism by using dynamic nuclear polarization to transiently enhance the signal for molecular probes that can assess different aspects of tumor metabolism. A recent feasibility study in participants with diffuse intrinsic pontine glioma demonstrated the safety of HP [1-13C]pyruvate injection and characteristic conversion to [1-13C]lactate and [13C]bicarbonate in the brain as biomarkers of glycolysis and oxidative phosphorylation respectively; however, the study was closed prematurely due to poor accrual [93] . Despite promises of HP [1-13C] MRI, the short lifetime of 13C magnetization requires very tight study logistics which can be challenging in pediatric glioma patients.…”
Section: Radiomics Radiogenomics and Multi-omics Approachesmentioning
confidence: 99%
“…Hyperpolarized carbon-13 (HP-13C) MR imaging presents a promising relatively new technique that allows noninvasive investigation of in vivo tumor metabolism by using dynamic nuclear polarization to transiently enhance the signal for molecular probes that can assess different aspects of tumor metabolism. A recent feasibility study in participants with diffuse intrinsic pontine glioma demonstrated the safety of HP [1-13C]pyruvate injection and characteristic conversion to [1-13C]lactate and [13C]bicarbonate in the brain as biomarkers of glycolysis and oxidative phosphorylation respectively; however, the study was closed prematurely due to poor accrual [93] . Despite promises of HP [1-13C] MRI, the short lifetime of 13C magnetization requires very tight study logistics which can be challenging in pediatric glioma patients.…”
Section: Radiomics Radiogenomics and Multi-omics Approachesmentioning
confidence: 99%
“…Balanced steady state free precession and concentric rings are also acquisition techniques that have been proposed for 3D imaging (Figure 6). 151,152 Among these, despite the frequent practice of EPSI, [153][154][155] metabolite-specific techniques (e.g., spectral-spatial excitation pulse followed by nonspectroscopic readout) are increasingly used in clinical research with hyperpolarized 13 C. 152,156,157 This is probably because clinical scenarios usually have determined targeting metabolites, making the nonspectroscopic readout techniques more time-efficient for clinical scenarios. 9 This is also evidenced by the adoption of spiral-based Dixon methods, which essentially consist of the acquisition of an extremely concise spectrum.…”
Section: Acquisition Techniquesmentioning
confidence: 99%
“…For brain studies, HP [1- 13 C]pyruvate has been applied in healthy controls [55,60]; patients with glioma [42,43,46], brain metastasis [42,63], and TBI [64]; and pediatric patients with CNS tumors [65]. In the following section, we will discuss these most recent clinical applications.…”
Section: Emerging Human Brain Applications Of Dynamic Hyperpolarized 13 C Metabolic Imagingmentioning
confidence: 99%
“…Other [1- 13 C]pyruvate HP 13 C MR metabolic brain imaging studies also include (1) safety and feasibility study in pediatric patients with CNS tumors (diffuse intrinsic pontine glioma, DIPG; craniopharyngioma; medulloblastoma) [ 65 ]. This study demonstrated preliminary safety profile in 6 patients at dosages of 0.34 and 0.43 mL/kg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation